The effects of Mucuna pruriens on the renal oxidative stress and transcription factors in high-fructose-fed rats - Ulu, Ramazan; Gozel, Nevzat; Tuzcu, Mehmet; Orhan, Cemal; Yigit, Irem Pembegul; Dogukan, Ayhan; Şahin, Kazım (Pergamon-Elsevier Science Ltd, 2018)
In the present study, we evaluated the effects of M. pruriens administration on metabolic parameters, oxidative stress and kidney nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B) and nuclear factor (erythroid-derived 2)-like 2 (Nrf2) signaling pathways in high-fructose fed rats. Male rats (n = 28) were divided into 4 groups as control, M. pruriens, fructose, and M. pruriens plus fructose. All rats were fed a standard diet supplemented or no supplemented with M. pruriens (200 mg/kg/d by gavage). Fructose was given in drinking water for 8 weeks. High fructose consumption led to an increase in the serum level of glucose, triglyceride, urea and renal malondialdehyde (MDA) levels. Although M. pruriens treatment reduced triglyceride and MDA levels, it did not affect other parameters. M. pruriens supplementation significantly decreased the expression of NF-kappa B and decreased expression of Nrf2 and HO-1 proteins in the kidney. This study showed that the adverse effects of high fructose were alleviated by M. pruriens supplementation via modulation of the expression of kidney nuclear transcription factors in rats fed high fructose diet.
Keywords: Mucuna pruriens; High-fructose; Transcription factors